The Influence of Organizational Experience and Mental Readiness on Entrepreneurial Intentions of Management Students - Uhud Darmawan Natsir (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Abstract: This study aims to analyze the influence of organizational experience and mental readiness on entrepreneurial intentions in management students. Entrepreneurial intentions are one of the important aspects that can increase economic independence among students. Factors that can influence entrepreneurial intentions include organizational experience they gain during college and mental readiness in facing the challenges of the business world. This study uses a quantitative method with a survey approach to 150 management students at University State of Makassar. The results of the study indicate that organizational experience and mental readiness have a significant influence on entrepreneurial intentions. Students who are active in organizations and have good mental readiness tend to have higher intentions to become entrepreneurs.